Colossal magnetoresistance at room temperature in manganites and chromium chalkospinels - Abramovich, A.I.; Korolyova, L.I.; Michurin, A.V. (Functional Materials, 2006)
A colossal magnetoresistance (CMR) has been found near room temperature in manganite La₁/₃Nd₁/₃MnO₃ and in chromiun chalkogenide spinels xCuCr₂S₄-(1-x)Cu₀.₅AI₀.₅Cr₂S₄ at 0.05≤x≤.20. It attains 27% and 9% for the manganite in 8.4 kOe field. The CMR in these materials is supposed to be of the same nature and in associated with an inhomogeneous magnetic state caused by an intense s-d exchange.